Tratamento com canabidiol da infância à adolescência atenua alterações neurodesenvolvimentais induzidas pela exposição neonatal de camundongos a lipopolissacarídeo - Monteiro, Mayara de Matos Morais (2022)
Autism Spectrum Disorder (ASD) is a developmental disability defined as persistent impairments in social interaction, communication and the presence of restrictive, repetitive patterns related to behaviors, interests, or activities. The pathophysiology of ASD is still elusive, but we can highlight innate immune dysfunction and inflammation. In this context, lipopolysaccharide (LPS) is an endotoxin that activates the production of pro-inflammatory cytokines leading to low-grade systemic inflammation. The endocannabinoid system represents a neuromodulatory network, and its receptors are found in the nervous and immune systems, representing pharmacological targets for treating neurodevelopmental disorders. antioxidant and anti-inflammatory. Therefore, we conducted a study in male and female Swiss mice challenged with LPS on postnatal days (PNs) 3 (10μg/kg, IP.), 5 and 7 (50μg/kg, IP.), and subsequently treated with CBD (1 mg/kg, IP.) from childhood to adolescence (PN 25 to 40), to determine the effect of CBD treatment on behavior and neuroinflammatory changes. The behavioral tests performed were burying spheres, social interaction, open field, and working memory (Y maze) on days PN 25 and PN45. After behavioral tests, analyses of anti- and pro-inflammatory markers were performed, such as arginase activity, nitrite, interleukin-6 (IL-6), and TNF levels in brain areas, prefrontal cortex (PFC), hippocampus (HC), and cerebellum (CE). In the burying spheres test that evaluates repetitive behavior, animals of both sexes showed an increase in this behavior, which was reversed by CBD. Females showed deficits in the social interaction test, but CBD could not reverse this. The neurochemical results showed that exposure to LPS in males increased hippocampal arginase activity, which was reversed by CBD. In the hippocampus of females, we observed a reduction in nitrite levels that was reversed by CBD. IL-6 levels were increased in the hippocampus of males exposed to LPS and treated with CBD, as well as in the same brain area, females exposed to LPS showed a reduction in TNF. The results show that CBD treatment between childhood and adolescence can mitigate autism-related behaviors in male and female animals, whose mechanism mainly involves modulating anti-inflammatory pathways that seem to be potentiated in animals subjected to this animal model of autism.